2019
DOI: 10.1038/gim.2017.130
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function mutations in TDRD7 lead to a rare novel syndrome combining congenital cataract and nonobstructive azoospermia in humans

Abstract: PurposeComorbid familial nonobstructive azoospermia (NOA) and congenital cataract (CC) have not been reported previously, and no single human gene has been associated with both diseases in humans. Our purpose was to uncover novel human mutations and genes causing familial NOA and CC.MethodsWe performed whole-exome sequencing for two brothers with both NOA and CC from a consanguineous family. Mutation screening of TDRD7 was performed in another similar consanguineous family and 176 patients with azoospermia or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…Genomic DNA (gDNA) from peripheral blood samples was extracted using a QIAamp® DNA Blood Midi Kit (Qiagen; Hilden, Germany). The 13 probands were subjected to WES using the HiSeq2000 sequencing platform (Illumina Inc., San Diego, CA, USA) at the Beijing Genome Institute at Shenzhen, as described previously (He et al, 2017;Tan et al, 2017;Zhu et al, 2016). WES data analysis was performed using the Genome Analysis Toolkit (GATK; https://software.…”
Section: Wes and Variant Filteringmentioning
confidence: 99%
“…Genomic DNA (gDNA) from peripheral blood samples was extracted using a QIAamp® DNA Blood Midi Kit (Qiagen; Hilden, Germany). The 13 probands were subjected to WES using the HiSeq2000 sequencing platform (Illumina Inc., San Diego, CA, USA) at the Beijing Genome Institute at Shenzhen, as described previously (He et al, 2017;Tan et al, 2017;Zhu et al, 2016). WES data analysis was performed using the Genome Analysis Toolkit (GATK; https://software.…”
Section: Wes and Variant Filteringmentioning
confidence: 99%
“…We recently reported that mutations in the ribonucleoprotein/RNA granule component gene TDRD7 (OMIM: 611258) cause congenital cataracts, suggesting that regulators of post-transcriptional gene expression control have key function in vertebrate lens development and maintenance of transparency ( 17–21 ). Subsequent to our report, new human mutations in TDRD7 have been linked to cataract in independent studies ( 22 , 23 ). Moreover, a TDRD7 polymorphism has been associated with age-related cataracts in a Han Chinese population ( 24 ), and expression profiling analyses have demonstrated a significant downregulation of TDRD7 transcripts in human aged cataractous lenses ( 25 ), providing further evidence for the importance of this gene in lens development and homeostasis.…”
Section: Introductionmentioning
confidence: 64%
“…In total, 138,085 variants were detected in the affected individual. The most promising candidate variants were identified using criteria described in our previous studies . Briefly, candidate variants were considered a priority when they met the following criteria: frequency below 5% in three public databases; predicted to be deleterious; homozygous; and relevance to infertility phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…We performed targeted look‐up for M1AP variants in 243 subjects with SO and 223 subjects with normal fertility, described in our previous study . Subsequently, genomic DNA samples were subjected to WES as previously described, followed by Sanger sequencing. Reverse transcription polymerase chain reaction (RT‐PCR) and immunoblotting analyses were used to verify pathogenicity.…”
Section: Methodsmentioning
confidence: 99%